Gender and national differences in emotional intelligence and empathy - Pongrac, Jelena (Psihološka obzorja (Ljubljana), 2019)
The study focused on the relationship of emotional and cognitive components of empathy with emotional intelligence abilities (labelling, understanding, and regulating emotions). Since both emotional intelligence and empathy have important role in a person's socio-emotional health and well-being, we need to better understand the relations between these two related constructs. Additionally, having samples from two different countries enabled us comparison on the national level. Two samples of adults participated in the study, namely from Croatia (N = 138) and Portugal (N = 138). We found significant moderate correlations between empathy and emotional intelligence measures in both samples. Four dimensions from the Interpersonal Responsivity Index (IRI; empathic concerns, fantasy, personal distress and perspective-taking) had significant moderate correlations with each other, with similar patterns of correlations in both samples. The strongest correlations were found for the TEQ (affective component of empathy) and perspective-taking (cognitive component of empathy) and different emotional intelligence components. Participants in the Portuguese sample had higher scores on the emotional component of empathy (empathic care and the TEQ), while cognitive component (perspective-taking) was more expressed in the Croatian sample. Participants in the Portuguese sample also had higher scores on all three components of emotional intelligence than participants in the Croatian sample. Regardless of the nationality, women had higher scores on the measures of empathic care, fantasy, perspective-taking and the TEQ, while men scored higher on the measure of personal distress. Regarding emotional intelligence scales, women had higher results on the Perceive and Understand emotions scale.
Keywords: Croatia; cross cultural differences; čustvena inteligentnost; emotional intelligence; Emotional skills and competence questionnaire ESCQ; empathy; empatija; gender differences; Hrvaška; Indeks medsebojne odzivnosti IRI; Interpersonal reactivity index IRI; medkulturne razlike; Portugalska; Portugese; razlike med spoloma; Toronto empathy questionnaire TEQ; Torontski vprašalnik empatije TEQ; Vprašalnik emocionalne kompetentnosti ESCQ